Lower extremity injury and return to sports of elite taekwondo athletes - Lee, Jae-Yul; Park, Ki Jun (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2024)
Objective We attempted to analyze the characteristics of lower-extremity injuries that occur during training based on the sex and weight class of elite taekwondo (TKD) athletes and the effect of pain scores on the return to sports periods (RTSP). Methods and Methods: We included 198 elite TKD athletes who participated in January–December 2023 and were trained in Korea. Injury incidence rates (IIR) were expressed as Poisson rates with 95% confidence intervals per 1,000 h of training. One-way analysis of variance was conducted to determine the pain score and RTSP according to sex, weight, and injury type. In addition, we performed simple linear regression to determine the effects of pain score on the RTSP. Results The lower-extremities IIR was 2.45 injuries per 1000 training hours, including 0.77 contact and 1.68 non-contact injuries. The IIR was lower in male than in female athletes (p<0.001), the most common injuries occurred in the ankle (0.78) and knee(0.53). In addition, the ligament (0.99) and muscle (0.70) were the most common injury types. All athletes demonstrated significant differences in pain scores (p<0.001) and RTSP (p<0.001) based on the injury type. In addition, we observed a significant difference between the pain score (p<0.001) and RTSP (p=0.004) based on sex. For every 1-point increase in pain score, all athletes had a 1.43-day increase in RTSP. Conclusion These results can be used as data to develop injury prevention programs for TKD athletes and to determine their RTSP.
Keywords: Taekwondo; sports injury; lower extremity; return to sports